2021
DOI: 10.3389/fvets.2021.735680
|View full text |Cite
|
Sign up to set email alerts
|

Dog Pulling on the Leash: Effects of Restraint by a Neck Collar vs. a Chest Harness

Abstract: Leash pulling is a concern for dog owners and can be detrimental to the health and welfare of dogs. Neck-collars and back-connection harnesses are popular restraint types. Harnesses have been proposed as a better and more considerate option for canine health and welfare. Anecdotally, dogs pull more when wearing a back-connection harness; however, there is no scientific evidence for this perception. This study aimed to investigate how strongly dogs pull on the lead to achieve a food treat or toy under restraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…One possible explanation for this effect of weight on outing duration may be related to the force exerted by larger dogs while on-leash. Shih et al [41] found that dogs of greater size and weight exhibit more tension on-leash, and increased tension on the leash has been shown to negatively impact volunteers' satisfaction walking shelter dogs [42]. Thus, it is possible that caregivers on outings with larger dogs may have been less satisfied due in part to an inability to handle their dogs, resulting in earlier returns to the shelter.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this effect of weight on outing duration may be related to the force exerted by larger dogs while on-leash. Shih et al [41] found that dogs of greater size and weight exhibit more tension on-leash, and increased tension on the leash has been shown to negatively impact volunteers' satisfaction walking shelter dogs [42]. Thus, it is possible that caregivers on outings with larger dogs may have been less satisfied due in part to an inability to handle their dogs, resulting in earlier returns to the shelter.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study sample was small ( n = 30) and the harness manufacturer funded the research. More recently, Shih et al 93 . found dogs pulled significantly harder in back connection harnesses than neck‐collars in trials with food but not with toys.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study sample was small (n = 30) and the harness manufacturer funded the research. More recently, Shih et al 93 found dogs pulled significantly harder in back connection harnesses than neck-collars in trials with food but not with toys. This suggests that for larger, stronger dogs that pull or those with comorbid behaviours requiring modification, headcollars might be more effective than harnesses.…”
Section: Equipmentmentioning
confidence: 99%